Characteristics of body height and proportion in elementary school synchronized swimmers - Tanaka, C.; Homma, M.; Kawahara, T.; Murata, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2004)
Recently, body height is considered as one of the major elements for synchronized swimmers to acquire high performance score. The aim of the study was to compare body height and proportion of Japanese female synchronized swimmers in elementary school to age-matched normal female Japanese or other Caucasian populations, by using charts of body height and proportion of girls in Japan. Subjects were nationwide synchronized swimmers of forth to sixth grade in elementary school, who participated in the audition for executing with the committee of synchronized swimming in Japan Swimming Federation. Body height and sitting height were measured for these athletes to evaluate body proportion. On the other hand, the data of girls in Japanese and Caucasian populations evaluated by the previous studies were used for comparison. As a result, body height and proportion in synchronized swimmers were similar and superior to those of general Japanese, respectively. However, those values were lower and inferior to those of general Caucasians, respectively. There were a limited number of Japanese athletes who had the comparable body shape to normal Caucasian.